2006
DOI: 10.1111/j.1469-7998.2006.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of sika (Cervus nippon) in the New Forest and in the Purbeck region, southern England: is there evidence of recent or past hybridization with red deer (Cervus elaphus)?

Abstract: Sika Cervus nippon are native to Japan and East Asia but are now naturalized in many parks of the world, including Britain. In contrast to the substantial body of research on the extent of hybridization between sika and red deer Cervus elaphus in Scottish populations, there has been little genetic analysis of the English populations of sika. Sika in England still have a patchy and discontinuous distribution; populations are thus still genetically isolated and may be expected to show higher variability in genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Molecular markers also have been used to detect, quantify and to determine the age of hybridization and introgression events (Diaz et al, 2006;Lorenzen et al, 2006;Barilani et al, 2007); these events can have serious biological implications that affect evolutionary trajectories of species (Arnold, '92;Grant et al, 2005). Conservation and management of threatened species are hindered by the occurrence of hybridization, whether owing to natural or anthropogenic causes (Allendorf et al, 2001).…”
mentioning
confidence: 99%
“…Molecular markers also have been used to detect, quantify and to determine the age of hybridization and introgression events (Diaz et al, 2006;Lorenzen et al, 2006;Barilani et al, 2007); these events can have serious biological implications that affect evolutionary trajectories of species (Arnold, '92;Grant et al, 2005). Conservation and management of threatened species are hindered by the occurrence of hybridization, whether owing to natural or anthropogenic causes (Allendorf et al, 2001).…”
mentioning
confidence: 99%
“…The four British populations clustered with the Nagasaki population. Similarly, Díaz et al (2006) demonstrated high similarity in microsatellite genotypes between the New Forest and Dorset sika (both southern England) and sika from Nagasaki. This finding agrees with historical information, in that Nagasaki was the only Japanese port open to trade in the mid 19th Century (Goodman et al 2001).…”
Section: Sikamentioning
confidence: 86%
“…These considerations do not rule out some impurity in the introduced sika, but they do suggest it was not extensive. Finally, we note that despite generally low levels of genetic variation in sika, there is nevertheless some genetic variation between sika populations subjected to either molecular genetic (Swanson 1999;Díaz et al 2006) or morphometric (Putman and Hunt 1994) analysis. While this variation could be attributed to different levels of low-grade introgression from red, it could also be due to the initial genetic variation associated with the individuals used to found the populations during the various introduction events.…”
Section: Sikamentioning
confidence: 98%
See 2 more Smart Citations